2005
DOI: 10.1128/iai.73.1.635-637.2005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Gliotoxin in Experimental and Human Aspergillosis

Abstract: Gliotoxin was measured in the lungs (mean, 3,976 ؎ 1,662 ng/g of tissue) and sera (mean, 36.5 ؎ 30.28 ng/ml) of mice with experimentally induced invasive aspergillosis (IA), and levels decreased with antifungal therapy. Gliotoxin could also be detected in the sera of cancer patients with documented (proven or probable) IA.Aspergillus fumigatus, the saprophytic mold associated with the majority of cases of human invasive aspergillosis (IA), is known to produce a variety of secondary metabolites during invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
141
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(146 citation statements)
references
References 17 publications
(12 reference statements)
4
141
1
Order By: Relevance
“…In addition, Lewis et al showed that gliotoxin was present in sera and lungs of mice suffering from experimentally induced invasive aspergillosis by LC-MS analysis [15]. These authors also demonstrated that gliotoxin could be detected, by LC-MS, in cancer patients with either proven or probable invasive aspergillosis [15].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, Lewis et al showed that gliotoxin was present in sera and lungs of mice suffering from experimentally induced invasive aspergillosis by LC-MS analysis [15]. These authors also demonstrated that gliotoxin could be detected, by LC-MS, in cancer patients with either proven or probable invasive aspergillosis [15].…”
Section: Introductionmentioning
confidence: 83%
“…While this approach is acceptable, the number of fungal metabolites which can be present in organic extracts, combined with the possibility of peptide generation due to unwanted proteolysis, demands a more rigorous confirmation of gliotoxin presence. LC-MS analysis of gliotoxin fulfils this criterion; however, this is a relatively specialised technique and is not available to all researchers [12,15,16]. Moreover, alternative bioassay formats have also been proposed for detection of gliotoxin and related epipolythiodioxopiperazines, of fungal origin, at levels of 18-20 ng well −1 [19,25].…”
Section: Discussionmentioning
confidence: 99%
“…Gliotoxin is necessary for maximal virulence in experimental mouse models of invasive pulmonary aspergillosis [16,17]. Furthermore, it is detectable in the serum of patients with invasive aspergillosis, suggesting that it also contributes to the pathogenesis of this disease in humans [18]. …”
Section: Introductionmentioning
confidence: 99%
“…48 This compound, which has a broad spectrum of immunosuppressive activities in animals and humans, 49 was recently determined in the lungs and sera of mice with experimentally induced aspergillosis. 50 It was also detected in the sera of human cancer patients with documented invasive aspergillosis. Tandem mass spectrometry in negative ion mode and selective reaction monitoring electro spray ionization (ESI) were used in this study.…”
Section: The Importance Of Secondary Fungal Metabolites: Mycotoxins Amentioning
confidence: 96%
“…These findings led the authors to speculate on the role of secreted metabolites in the pathogenesis and persistence of opportunistic infections. 50 An immunoassay detection clinically more acceptable than mass spectral approaches has therefore been developed: gliotoxin and helvolic acid were conjugated to thyroglobulin for antisera generation in rabbits as well as to bovine serum albumin (BSA). 51 The antiserum could then be subsequently used for the detection of both free and conjugated haptens.…”
Section: The Importance Of Secondary Fungal Metabolites: Mycotoxins Amentioning
confidence: 99%